PERAN TIKTOK DALAM PELESTARIAN TARI PERSEMBAHAN SEBAGAI IDENTITAS BUDAYA LOKAL - Dharmawan, Mukti; Rizki Amalia, Haifa; Naufal Haykal, Muhammad; Agustina, Yesi; Titasari Bangun, Elsi (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2026)
This study examines the role of TikTok social media as a means of preserving the Tari Persembahan, one of the traditional dances of Melayu Riau, in building local cultural identity among students at SMK Hasanah Pekanbaru. The background of this study is based on the increasing use of TikTok among teenagers, which not only functions as a medium of entertainment but also as a space for cultural expression and creative participation among the younger generation. This phenomenon opens up strategic opportunities for the use of digital media in efforts to preserve traditional arts and culture, which are beginning to experience a decline in interest. This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, documentation, and literature studies. The research informants consisted of female students who were active in traditional dance extracurricular activities and arts and culture teachers who acted as mentors. The data was analyzed thematically to identify patterns of perception, motivation, involvement, and challenges in the use of TikTok as a medium for cultural preservation. The results show that TikTok is able to increase students' interest and involvement in the Tari Persembahan through the presentation of visual content that is attractive, easily accessible, and relevant to the daily lives of teenagers. Although student involvement in content production is still limited, high enthusiasm is evident when students are directly involved in making dance videos. The role of teachers has proven to be crucial in guiding the technical aspects of dance while instilling the cultural values contained in each movement. This study concludes that the structured use of TikTok in extracurricular cultural arts activities can be an adaptive cultural preservation strategy in the digital age. These findings emphasize the importance of digital literacy and educator guidance in ensuring that social media not only functions as entertainment but also as a means of strengthening the cultural identity of the younger generation.